Predictors of Seronegative Conversion After Centralized Management of Syphilis Patients in Shenzhen, China - Luo, Zhenzhou; Ding, Yi; Yuan, Jun; Wu, Qiuhong; Tian, Lishan; Zhang, Li; Li, Bo; Mou, Jinsong (Frontiers in Public Health, 2021)
Objective: The aim of this study was to explore the seronegative conversion status of syphilis patients after centralized management and to analyze potential determinants. Materials and Methods: A retrospective population-based cohort study was conducted, and data for individuals who had been diagnosed with syphilis between 2011 and 2019 were retrieved from the Shenzhen Nanshan Center for Chronic Disease Control. Seroconversion statuses were summarized as percentages. Univariable and multiple Cox proportional hazard regression models were used to analyze the factors associated with seronegative conversion among syphilis patients. Results: During the study period, 1,545 patients with syphilis participated in the syphilis convergence case management program on a voluntary basis, of whom 290 were excluded due to missing follow-up data. A total of 27.6% (346/1255) of patients with syphilis showed seronegative conversion. Multivariable analysis revealed that the following significantly determined syphilis seroconversion from positive to negative: younger age (15–19 years vs. ≥30 years: HR = 2.18), male gender (HR = 1.45), lower baseline toluidine red unheated serum test (TRUST) titer of ≤ 1:8 (HR = 2.23), and different disease stages, including latent syphilis (HR = 1.98), primary syphilis (HR = 7.67), and secondary syphilis (HR = 4.83). Conclusions: Few patients with syphilis tested negative after treatment at the end of the study. Seronegative conversion in the patients was associated with age, sex, baseline TRUST titer, and syphilis stage.